Analysis of the Learning Interest Profile of Fourth-Grade Students at MI Nurul Islahil Islami in the IPAS Subject in the 2024–2025 Academic Year - Baiq Dila Sari Dewi (Lombok Institute, 2025)
This study aims to examine the learning interest profile of fourth-grade students at MI Nurul Islahil Islami in the Integrated Science and Social Studies (IPAS) subject in the 2024–2025 academic year. The research employed a quantitative, descriptive method. The research subjects were all 29 fourth-grade students, determined using a total sampling technique. The data collection instrument was a closed-ended questionnaire with two response options (